Continuous Theta-Burst Stimulation in Children With High-Functioning Autism Spectrum Disorder and Typically Developing Children - Jannati, Ali; Block, Gabrielle; Ryan, Mary A.; Kaye, Harper L.; Kayarian, Fae B.; Bashir, Shahid; Oberman, Lindsay M.; Pascual-Leone, Alvaro; Rotenberg, Alexander (Frontiers in Integrative Neuroscience, 2020)
Objectives: A neurophysiologic biomarker for autism spectrum disorder (ASD) is highly desirable and can improve diagnosis, monitoring, and assessment of therapeutic response among children with ASD. We investigated the utility of continuous theta-burst stimulation (cTBS) applied to the motor cortex (M1) as a biomarker for children and adolescents with high-functioning (HF) ASD compared to their age- and gender-matched typically developing (TD) controls. We also compared the developmental trajectory of long-term depression- (LTD-) like plasticity in the two groups. Finally, we explored the influence of a common brain-derived neurotrophic factor (BDNF) polymorphism on cTBS aftereffects in a subset of the ASD group. Methods: Twenty-nine children and adolescents (age range 10–16) in ASD (n = 11) and TD (n = 18) groups underwent M1 cTBS. Changes in MEP amplitude at 5–60 min post-cTBS and their cumulative measures in each group were calculated. We also assessed the relationship between age and maximum cTBS-induced MEP suppression (ΔMEPMax) in each group. Finally, we compared cTBS aftereffects in BDNF Val/Val (n = 4) and Val/Met (n = 4) ASD participants. Results: Cumulative cTBS aftereffects were significantly more facilitatory in the ASD group than in the TD group (PFDR’s < 0.03). ΔMEPMax was negatively correlated with age in the ASD group (r = −0.67, P = 0.025), but not in the TD group (r = −0.12, P = 0.65). Cumulative cTBS aftereffects were not significantly different between the two BDNF subgroups (P-values > 0.18). Conclusions: The results support the utility of cTBS measures of cortical plasticity as a biomarker for children and adolescents with HF-ASD and an aberrant developmental trajectory of LTD-like plasticity in ASD.